2021
DOI: 10.3390/ijerph18126241
|View full text |Cite
|
Sign up to set email alerts
|

The Childhood Cancer Centre Is Coming Home: Experiences of Hospital-Based Home Care

Abstract: Today, there is a shift towards care being given closer to the patient, with more children receiving care in their homes. Care at home has proven to be a viable alternative to hospital care, as shown by a project for hospital-based home care conducted in West Sweden. The aim of this study was to describe how children with cancer and parents experienced receiving care at home. After purposive sampling, six children with cancer aged 6–16 and eight parents participated. Semistructured interviews were performed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Consistent with previous research, 28,3639 our overarching theme demonstrates that mutual trust within and between families and professionals has a profound impact on the overall experience of the collaboration and quality of care. Lack of trust induced insecurity and, ultimately, could lead to reluctance to collaborate.…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with previous research, 28,3639 our overarching theme demonstrates that mutual trust within and between families and professionals has a profound impact on the overall experience of the collaboration and quality of care. Lack of trust induced insecurity and, ultimately, could lead to reluctance to collaborate.…”
Section: Discussionsupporting
confidence: 83%
“…They assumed to reestablish the normal of living by making positive changes in their routine lives. This is consistent with ndings of other studies that reported being able to adapt and accept ongoing changes were effective coping strategies (25)(26)(27).…”
Section: Cope Strategies Of Parents Whose Children Are Diagnosed With...supporting
confidence: 92%
“…Parents who used the tablet experienced savings in time and effort, and they said that care activities at home were affordable (i.e., worth the time, money, and energy that they spent). The use of home-based pediatric care has previously been presented as a safe and cost-effective, whether as a complement or an alternative to hospital care [30]. Cost-effectiveness in using eHealth has been identified in other age groups of patients, such as the elderly [31].…”
Section: Discussionmentioning
confidence: 99%